The death of Yugoslavia (Kuala Lumpur : Radio TV Malaysia, 1996)
The program covers documentary and interviews on the present political aspects of Yugoslavia. This program was aired by RTM 1, beginning on 16/4/1996 at 11.00 pm. and the series ended on 20/4/1996
vol.1. Enter nationalism - vol.2. Death of Yugoslavia - vol.3. Wars of independent - vol.4. The gates of hell - vol.5. A safe area
Keywords: Yugoslavia -- Politics and government